What does the literature say about the needs of veterans in the areas of health?. (December 2016) - Hynes, Celia; Thomas, Mike
Abstract: This paper reports on a systematic review undertaken in 2013 aimed at identifying evidence and dismissing some of the myths surrounding the needs of the veteran community. Papers were retrieved from a wide range of sources to ensure that literature covered the key areas of health concerns and focused also on time spent in service. Of the twenty eight papers reviewed categories relating to mental health (including PTSD and suicide), the use of alcohol, trauma, hearing loss, cancer and obesity were identified. Outcomes from the review established that while early service leavers were the most vulnerable there were also aspects within service that had an impact on future life events such as the type of leadership experienced, the cohesion of the unit and facing combat situations. The use of alcohol as a coping mechanism is also considered prevalent with adverse effects as is the worry of family situations at home. The impact of service life on the veteran, especially if suffering trauma will have long lasting psychological and physical outcomes, although it is recognised that veterans in the main have excellent physical and psychological strength and many physical illnesses are not greatly exaggerated from that of the general public. Highlights: Early service leavers are the most vulnerable group of the veteran community. Services for veterans should be more familiar with the military stressors There are often financial worries, concerns about child health and sometimes about partner fidelity which lead to anxiety and contribute to depression Reservists are more likely to suffer mental health problems. Good leadership and good unit cohesion reduce anxiety and mental health problems.